Notes to build an analytical method from Queer Legal Feminism - Sánchez-Moreno, Manuel (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2022)
Feminisms put the focus on Human Rights to say that equality and universality has been built leaving out certain subjects, such as women or affective-sexual diversity. Critical theory also addresses rights and subjects, within the framework of social struggles. All this shed new light, to first questioning the construction of law and, later, to build and interpret laws considering all humanity. The identities excluded previously, claim now a greater presence and underrepresented experiences. Feminisms have discovered that Law is an area of heterocispatriarchy and that the Law and its interpretation must contemplate experiences of traditionally excluded people. The Feminisms develops tools to demonstrate the lack of protection and invisibility before the Law. Starting from the Feminist theoretical proposals and an evolution of the Standards, the main causes of this legal bias such as forclusion or foundationalism are analyzed. Elements that are considered key to avoid an essentialist analysis, such as intersectionality, the inclusion of LGTBIQA+ people or the manifestations of sexism will also be retaken. Finally, a Queer Legal Feminism methodology will be proposed as a starting point for analysis, interpretation and formulation of gender-sensitive normative texts. We will follow studies of Iris Young, Martha Nussbaum, Catharine Mackinnon, Nancy Fraser, Margrit Eichler or Alda Facio.